Pengaruh Good Corporate Governance terhadap Tax Avoidance dengan Manajeman Laba Sebagai Variabel Intervening pada Perusahaan IDX BUMN 20 yang Terdaftar di BEI Tahun 2018-2022 - Khaerani Pramudita, Bannati; Robinson (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to analyze and determine the influence of good corporate governance on tax avoidance with earnings management as an intervening variable. This research uses a quantitative approach and the data used is secondary data. The population in this study were 11 companies included in the idxbumn20 index published on the Indonesia Stock Exchange for the 2018-2022 period, so a sample of 55 was obtained. The data analysis technique used the Partial Least Square method with the Smart PLS 4.0 software tool. The results of the research show that the good corporate governance variable has a positive effect on earnings management, good corporate governance has a negative effect on tax avoidance, earnings management has a negative effect on tax avoidance, and finally, earnings management can mediate the significant influence of good corporate governance on tax avoidance in a negative direction.